Caloric Restriction Increases Serum Testosterone Concentrations in Obese Male Subjects by Two Distinct Mechanisms - Schulte, D. M.; Hahn, M.; Oberhäuser, F.; Malchau, G.; Schubert, M.; Heppner, C.; Müller, N.; Güdelhöfer, H.; Faust, M.; Krone, W.; Laudes, M. (Hormone and Metabolic Research, 2014)
The concentration of serum testosterone is mainly regulated by the testicular function, which is under control of the central hypothalamic-pituitary-gonadal axis. A certain amount of testosterone is converted into β-estradiol by adipose tissue. Obesity in men is often associated with decreased androgen levels. The aim of the present study was to examine the effect of caloric restriction on serum testosterone levels in obese men. Dietary intervention study was performed with a very low calorie diet (800 kcal/d) for 12 weeks. Thirteen obese human male subjects (median body mass index: 42.7 kg/m2) were included. Body composition was assessed by impedance analysis. Insulin sensitivity was estimated by leptin-to-adiponectin ratio (LAR). Testosterone (T), β-estradiol, albumin, sex hormone-binding globulin (SHBG), LH, and FSH serum concentrations were measured by enzyme immunoassays. Statistical analysis was performed on baseline and values after 3 months. Caloric restriction significantly increased total testosterone (6.97 nmol/l to 13.21 nmol/l; p=0.001) and SHBG (22.11 nmol/l to 42.12 nmol/l; p=0.001) concentrations in serum. This is caused by a significant improvement of the testicular function (LH/T: 0.36–0.20; p=0.005) and a significant reduction of the T/β-estradiol conversion rate (73.59–104.29; p=0.003). There was a significant negative correlation of improvement of testicular function and LAR (rs=−0.683 (p=0.042)). In obese men caloric restriction significantly increases the serum testosterone concentration. This is achieved by 2 distinct mechanisms, that is, improvement of testicular function and reduced conversion of testosterone to β-estradiol by aromatase activity of the adipose tissue.
Keywords: obesity; testosterone; inflammation; nutritional intervention